The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2016
DOI: 10.1051/0004-6361/201527468
|View full text |Cite
|
Sign up to set email alerts
|

ATLASGAL: A Galaxy-wide sample of dense filamentary structures

Abstract: Context. Filamentary structures are ubiquitous in the interstellar medium. Investigating their connection to the large-scale structure of the Galaxy and their role in star formation is leading to a paradigm shift in our understanding of star formation. Aims. We study the properties of filamentary structures from the ATLASGAL survey, which is the largest and most sensitive systematic ground-based survey of the inner Galactic plane at submillimeter wavelengths. Methods. We use the DisPerSE algorithm to identify … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
156
1

Year Published

2016
2016
2018
2018

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 111 publications
(160 citation statements)
references
References 111 publications
(194 reference statements)
3
156
1
Order By: Relevance
“…These filaments are observed at various scales and often contain the starforming clumps and cores along their lengths (e.g. Schneider et al 2012;Ragan et al 2014;Contreras et al 2016;Li et al 2016, and references therein). However, the physical mechanisms concerning to their formation and their link to the star formation processes are not well understood.…”
Section: Introductionmentioning
confidence: 99%
“…These filaments are observed at various scales and often contain the starforming clumps and cores along their lengths (e.g. Schneider et al 2012;Ragan et al 2014;Contreras et al 2016;Li et al 2016, and references therein). However, the physical mechanisms concerning to their formation and their link to the star formation processes are not well understood.…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, ATLASGAL provides high angular resolution at a wavelength sensitive to the cold dust and is unaffected by background contamination and saturation, which complicate the analysis of Hi-GAL data. On the other hand, Hi-GAL is more sensitive to emission from low-density structures, down to values of ∼10 21 cm −2 at 16 K, while ATLASGAL has a 5-σ column density sensitivity of ∼7.5×10 21 cm −2 for a dust temperature of 20 K. Li et al (2016) identified twelve filamentary structure candidates in the SEDIGISM science demonstration field based on the ATLASGAL data, nine of which are single filament candidates (elongated linear structures with typical aspect ratios larger than three), and the other three being networks of filaments (several filaments that seem to be connected to each other). A study of Hi-GAL column density map of the region reveals 88 filament candidates.…”
Section: Filament Candidates In Atlasgal and Hi-galmentioning
confidence: 95%
“…Recently, the ATLASGAL and Hi-GAL surveys were used to identify filament candidates in the Galactic plane through the analysis of their continuum emission at 870 µm (Li et al 2016), and at 70, 160, 250, 350 and 500 µm (Schisano et al 2014;Wang et al 2015), respectively. The two surveys deliver a unique dataset to compile an unbiased catalogue of filament candidates throughout the Galaxy.…”
Section: Filament Candidates In Atlasgal and Hi-galmentioning
confidence: 99%
See 1 more Smart Citation
“…In starforming regions, the filamentary structures often harbor dense massive star-forming clumps and young stellar clusters (e.g. André et al 2010André et al , 2016Schneider et al 2012;Ragan et al 2014;Kainulainen et al 2016;Contreras et al 2016;Li et al 2016, and references therein). However, the role of filaments in the star formation process (including massive stars) is still a matter of debate (e.g.…”
Section: Introductionmentioning
confidence: 99%